Design of static wireless charging coils for integration into electric vehicle - Tan, Y. K. (2013)
This paper analytically discusses various factors that affects static wireless charging of an electric vehicle and also presents the maximum efficient operating regime of this wireless power transfer. The main goal of this paper is using magnetic resonance to supply power wirelessly via air and to determine the dependency of power supply on coil dimensions and other factors. Different types of source and load coils are analyzed like circular, spiral and helical. Different shapes of the coils are also taken into account like square and circular. From the analysis, it is found that the efficiency of power transfer is derivable by the equivalent circuit point of view and also using coupled mode theory. The analysis shows that the efficiency is dependent on the coil radius, distances between the coils and the Q-factors of the coils. From the analysis, an overview of the optimum design of the coils and distance between the coils has been given.